Duck plague virus US3 kinase phosphorylates and induces STING degradation to inhibit innate immune responses - Bin Tian; Yanming Tian; Dongjie Cai; Huanhuan Cao; Liping Wu; Mingshu Wang; Qiao Yang; Ying Wu; Renyong Jia; Dekang Zhu; Mafeng Liu; Shun Chen; et al. (Poultry Science)
Duck plague virus (DPV) causes the highest mortality rate among aquatic birds; however, its antago nistic mechanism against antiviral innate immune responses remains elusive. In this study, we systematically screened and found that most DPV genes have inhibitory potential for duck cyclic guanosine monophosphate-adenosine monophosphate synthetase (cGAS)/stimulator of interferon (IFN) gene (STING) pathway-mediated antiviral responses, with the DPV US3 kinase showing the strongest inhibitory activity. Co-immunoprecipitation and immunoblotting assays demonstrated that DPV US3 interacted with STING and induced its degradation. Further mutagenesis experiments revealed that DPV US3 kinase activity was essential for phosphorylating STING, reducing STING dimerization, and inhibiting STING-mediated antiviral responses. Sequence alignment and mutagenesis studies have demonstrated that DPV US3 phosphorylates STING at serine 86, near the Endoplasmic reticulum (ER) retention sequence (R82YRGS86), disrupting its association with tank-binding kinase 1 (TBK1) and inducing STING degradation. Finally, US3 knockout attenuated DPV replication by activating higher levels of IFN and ISGs in vitro and in vivo. These results demonstrate that DPV promotes viral infection and pathogenicity by inducing STING degradation through the encoded US3 kinase, providing new insights into the mechanism of DPV immune evasion.